Study on bacterial isolation from dogs affected with malignant tumor: Saher. M.H. , Mohamed .A .Abdulrazak , Ali.S. Aboud , Al-khaban. J. M. , and Iesa. A.M - H., Saher M. (The Iraqi Journal of Veterinary Medicine, 2009)
To identify the bacterial isolation from dogs have cancer diseases, the samples were (throat swab and urine) havebeen taken from (64) dogs suffering from different cancer diseases includes (38) females and (26) males.The result of throat swab as were follows: E.coli (50%), Actenomyces pyogenes (40.6 %) , Beta HeamolyticStreptococcus group D (21.8 %) , Staphylococcus aureus (21.8 %), Klebsiella spp also Actenomyces viscosus(18.7%), S.epidermidis(12.5%), Beta Heamolytic Streptococcus groupG (9.3 %) , Proteus mirabilis (9.3 %) ,Beta Heamolytic Streptococcus group B (6.2 %) , Bacillus subtilis (6.2 %), Micrococcus (6.2%) ,Pseudomonas aerugenosa also Proteus vulgaris (3.1%).While the urine samples of infected doges showed the bacterial isolates of Escherichia coli (53.12 %) ,Staphylococcus aureus (28.1) , Proteus mirabilis (23.4%) , Klebsiella spp (18.7 %) , Proteus vulgaris alsoStaphylococcus saprophyticus (7.8 %), Staphylococcus epidermidis (6.2 %) , Micrococcus , Actenomycespyogens, Pseudomonas aerugenosa ( 3.1 %) . No significant differences were appeared at level P> 0.05between females and males or Gram positive and Gram negative bacteria.The results of antibiotic sensitivity test to bacterial isolates from throat swabs were: E.coli have been showed asignificant differences at level P <0.05 among different antibiotics, the highest was amikacin and lowest wastetracycline.Actenomyces pyogens has been significant differences at level P <0.05 among different antibiotics, the highestwas amikacin, ampicillin,ciprofloxacin & the lowest was amoxicillin.Beta Heamolytic Streptococcus group D has been no significant differences at level P >0.05 among differentantibiotics.The results of antibiotic sensitivity test to bacterial isolates from urine samples showed: E.coli have beensignificant differences at level P <0.05 among different antibiotics, the highest was amikacin and augmantin butthe lowest was clarithromycin.S. aureus has been significant differences at level P <0.05 among different antibiotics, the highest were amikacin,cefotaxime & augmantin but the lowest was tetracycline.P.mirabilis has been significant differences at level P <0.05 among different antibiotics, the highest was amikacin,the lowest were ampicillin, clarithromycin, amoxicillin & tetracycline..